(untitled) (Revista de Ciências Agroveterinárias, 2022)
Soybean is one of the most demanding annual crops in boron (B), however, there is a divergence regarding the best phenological stage to carry out this application via foliar. Therefore, the objective of the present work was to evaluate the influence of different times of foliar application of B, with and without splitting, on flowering, productivity, and components of soybean production. For this, an experiment was carried out in the field, the experimental design used was in randomized blocks, with seven times of foliar applications of B (control, 100% 15 V4, 100% R1, 100% R3, 50% V4 + 50% R1, 50% V4 + 50% R3 and 50% R1 + 50% R3) and four replications, totaling 28 experimental plots. The number of flowers, number of beginning pod, B content in plants, weight of 1000 grains (g) and productivity were analyzed. The highest B content was observed with applications in the V4 (50%) + R1 (50%) and V4 (50%) + R3 (50%) stages, that is, part in the vegetative stage and part in the reproductive stage. The application of B did not result in a significant difference in relation to the number of inflorescences per plant. There was no significant effect of the times of foliar application of B for the variable of number of pods per plant, number of inflorescences and productivity. For weight of 1000 grains (g) higher values ​​were found in V4, R1 and R3 and in the control. Therefore, the foliar application of boron in the stages V4 (50%) + R1(50%) and V4(50%) + R3 (50%) increased the levels of B in the plant, while in R1+R3 it provided the highest number of beginning pods. However, there was no effect of boron application for grain yield regardless of the time of application.